1989
DOI: 10.1002/j.1460-2075.1989.tb03538.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel spatial transcription pattern associated with the segmentation gene, giant, of Drosophila.

Abstract: The segmentation gene, giant, is located in 3A1 within a cloned chromosome region surrounding the zeste locus. Rearrangement breakpoints associated with giant mutations were localized on the genomic clone map, and nearby transcription units were identified. One transcription unit is active during early embryogenesis and its transcripts are spatially localized from blastoderm into extended germband stages, consistent with expected expression patterns predicted by the 'gap' phenotype of giant mutants. Germ line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
3

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 30 publications
5
65
1
3
Order By: Relevance
“…Double stain experiments (data not shown) indicated that the timing and spatial regulation of both patterns are indistinguishable from the anterior expression domains of the endogenous gt gene (Fig. 2 A and C) (24). We also identified a CRM 3Ј of the gap gene tll (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Double stain experiments (data not shown) indicated that the timing and spatial regulation of both patterns are indistinguishable from the anterior expression domains of the endogenous gt gene (Fig. 2 A and C) (24). We also identified a CRM 3Ј of the gap gene tll (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…One potential candidate for such a novel activator was the segmentation gene giant (gtl. gt is a zygotic X-linked gene expressed in an anterior and posterior domain at the time of Sxl activation [Mohler et al 1989;Eldon and Pirrota 1991; Kraut and Levine 1991 ). Thus, gt is capable of providing positional information in the regions where runt does not.…”
Section: Discussionmentioning
confidence: 99%
“…2). However, the gt À phenotype is not as strong as observed for other gap genes null alleles (Mohler et al, 1989). It is possible that other factors also participate in the regulation of the same targets and counter-balance the absence of gt (Mohler et al, 1991).…”
Section: Gt Partners In the Regulation Of The Striped Patternmentioning
confidence: 80%
“…The gt loss of function alleles or gt deficiencies cause defects in the posterior half of the larva and in the head region (Gergen and Wieschaus, 1986;Mohler et al, 1989). The defects observed in the cuticle could reflect the deviation of a group of anterior and posterior stripes pattern in the mutant (Fig.…”
Section: Gt Partners In the Regulation Of The Striped Patternmentioning
confidence: 99%
See 1 more Smart Citation